Pengaruh Komunikasi Persuasif Guru Terhadap Motivasi Belajar Siswa Kelas X SMKN 1 Sumbar Pada Masa Pandemi Covid-19 - Andre Mahendra; Indria Flowerina (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2021)
The spread of the corona virus pandemic or Covid-19 has presented its own challenges for educational institutions in Indonesia, one of which is SMKN 1 West Sumatra, which is one of the vocational education institutions in the city of Padang. In the online learning process, many students' grades do not understand the material taught by the teacher and there is a problem with declining grades in students. When students are in a condition of not having the motivation to learn, this is where the role of the teacher is to motivate students, one of which is persuasive communication techniques. The purpose of this study was to proportionally reveal the influence of teacher persuasive communication on student motivation at SMKN 1 West Sumatra during the Covid-19 pandemic. This research uses quantitative research. The sampling technique is a simple random sampling technique. The sample of this research is class X students of SMKN 1 West Sumatra, totaling 84 students. Simple linear regression analysis was used to test the hypothesis with the SPSS 24 program. The results of this study indicate that the teacher's Persuasive Communication variable is in the Good Enough category. The results indicate that there is an influence between teacher persuasive communication and student learning motivation during the Covid-19 pandemic. Learning activities in the teacher's classroom tend to use persuasive communication, to direct student behavior in the teacher's classroom applying a democratic and permissive discipline model. The teacher does not give heavy sanctions, but is more dominant in directions and advice that moves students' motivation to do better.